Pendidikan Agama Islam pada Anak Jalanan dan Anak Terlantar di Pondok Pesantren Al-Fataa Bantul Yogyakarta - Munjahid (AN NUR: Jurnal Studi Islam, 2015)
Implications of Islamic Education on street children and abandoned children in al- Fataa children’s boarding school are: Pupils able to mention the names and types of vowel, reading Arabic numbers from 1-500, reading Arabic-Indonesian transliteration, reading passages from the Koran smoothly, apply the science of Tajweed and recitation Garib well. Pupils have an attitude and good skills in terms of: self-awareness, to overcome the crisis, independent study, a good relationship with other people, can judge for itself, establish the identity of a positive, self-controlled, functioning self, communicate, understand the needs and feelings of others, sensitive and open in communicating, concentrating consciousness, creative, combining cognitive and affective learning rate. While the humanist values that are less able to have is the ability imaginative. In conjunction with this ability, most students are less able to read the Qur’an with a good voice and songs